2005
DOI: 10.1152/ajpheart.00134.2005
|View full text |Cite
|
Sign up to set email alerts
|

Increased aortic stiffness in the insulin-resistant Zuckerfa/farat

Abstract: Accumulating clinical evidence indicates increased aortic stiffness, an independent risk factor for cardiovascular and all-cause mortality, in type 2 diabetic and glucose-intolerant individuals. The present study sought to determine whether increased mechanical stiffness, an altered extracellular matrix, and a profibrotic gene expression profile could be observed in the aorta of the insulin-resistant Zucker fa/fa rat. Mechanical testing of Zucker fa/fa aortas showed increased vascular stiffness in longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 35 publications
5
26
0
3
Order By: Relevance
“…Diabetes causes overproduction of cardiac ECM, which contributes to diastolic dysfunction, and ECM overaccumulation has been reported in the diabetic rat heart (Martin et al, 2005). Studies have shown that collagen IV and fibronectin coalesce around smooth muscle cells in the aortic media (Sista et al, 2005). In this study, mRNAs corresponding to these major ECM components were increased in experimental diabetes (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Diabetes causes overproduction of cardiac ECM, which contributes to diastolic dysfunction, and ECM overaccumulation has been reported in the diabetic rat heart (Martin et al, 2005). Studies have shown that collagen IV and fibronectin coalesce around smooth muscle cells in the aortic media (Sista et al, 2005). In this study, mRNAs corresponding to these major ECM components were increased in experimental diabetes (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…[23][24][25] In addition, mechanical testing of the aortas from obese Zucker (fa/fa) rats showed greater stiffness in the circumferential and longitudinal directions. 26 However, the mechanistic insight into the link between obesity and aortic stiffening has been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…RASMCs were harvested by enzymatic digestion from rat aortas as previously described (53). Cells were cultured in Dulbecco modified Eagle medium with 10% fetal bovine serum, 10 units/ml penicillin, and 100 μg/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%